Overcoming Barriers to Digital Payment: Insights from QRIS Adoption in Rural West Sulawesi - Gunawan Purbowo; Irwan Trinugroho (Journal of Management and Entrepreneurship Research, 2025)
Objective: We examine the key factors influencing QRIS adoption in rural West Sulawesi, focusing on access to information, infrastructure availability, user perceptions, and financial literacy. Research Design & Methods: We applied a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data from 410 respondents. Constructs were based on the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT). Findings: We found that QRIS adoption is significantly influenced by access to information, infrastructure, and user perceptions. While financial literacy does not have a significant direct effect. Among the control variables, age and education show significant positive relationships with adoption, whereas gender and spending levels have no direct impact. Implications and Recommendations: Improving ICT infrastructure and promoting targeted information campaigns can enhance QRIS adoption. Policymakers should leverage community leaders and educational programs to build trust and positive perceptions, while focusing on younger and educated demographics to act as digital ambassadors. Contribution & Value Added: Our research highlights the critical role of infrastructure, social influence, and user perceptions over financial literacy in driving digital payment adoption, providing actionable insights for enhancing financial inclusion in rural contexts.